BURROW DECREASING-UPWARD PARASEQUENCE (BDUP): A CASE STUDY FROM THE LOWER JURASSIC OF THE TRENTO CARBONATE PLATFORM (SOUTHERN ALPS), ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
A study of the Trento carbonate platform (Southern Alps, Italy) identified a different type of parasequence named "burrow decreasing- upward parasequence" (BDUP). This important type of bioturbated shallowing-upward sequence, 2.3-2.9 m thick, developed in a warm lagoonal environment and characterizes the Pliensbachian interval of the Calcari Grigi Formation. The study of surficial bioturbation and three-dimensional, Y-shaped deep burrows in the BDUP (produced mainly by crustacean decapods) defined taphonomical characteristics and resulted in the identification of four types of Thalassinoides suevicus (Types I, II, III, IV). A detailed analysis of the burrows focused on the enlargement at the bifurcation point, on the development of the vertical burrow and on the coarse-grained skeletal debris infilling of the burrows. Surficial bioturbation affected only the first centimeters of the substrates and did not produce preservable trace fossils; it is recognizable by the taphonomic dislocation of shell beds and reorientation of skeletal remains. Bioturbation-burrowing analysis resulted in the identification of 19 "burrow decreasing- upward" parasequences (BDUP). They are ichnologically, taphonomically and sedimentologically well characterized, and represent a useful type for sequence stratigraphy in a carbonate platform environment dominated by biogenic activity.